Integrating Services in the Economic Fitness Approach - Zaccaria, Andrea (World Bank, Washington, DC, 2018)
Economic Complexity is a set of network-based and algorithmic methods for the study of economic development and competitiveness. In this framework, Economic Fitness is an innovative approach that improves the mathematical and conceptual scheme. For convenience, these methods were originally conceived on trade in goods. This paper extends the Economic Fitness methodology to include a trade in services element to yield a universal matrix of world trade and thus provide a more complete picture of a country's development and global competitiveness. The paper applies two algorithms to the universal trade in goods and services matrix to contrast country competitiveness and change in complexity and diversification when services are added to the traditional goods-only matrix. The results show that (i) the competitiveness of many countries was previously over- or underestimated, that is, many countries gain or lose positions in the ranking of economic fitness when services trade is considered alongside goods; and (ii) complex services tend to cluster with complex manufacturing, suggesting a common capabilities structure. These findings show how developing complex services aids diversification strategies for developing countries.